Realitas Pemenuhan Hak Penyandang Disabilitas di Lembaga Pemasyarakatan - Suparman Marzuki; Despan Heryansyah (Nagari Law Review, 2020)
To fulfill the rights of persons with disabilities in correctional institutions is an inseparable part of the paradigm of the integrated criminal justice system, which is also the spirit of Law No. 8 of 2016 concerning Persons with Disabilities, that the judicial process is an inseparable unit since the handling of cases by the police, prosecutors, the judiciary, up to the implementation of court decisions through the Ministry of Law and Human Rights. The court's decision in the form of imprisonment is carried out by a prison. However, even though Indonesia has ratified the Convention on the Rights of Persons with Disabilities and ratified Law No. 8 of 2016 concerning Persons with Disabilities, barriers to the fulfillment of the rights of persons with disabilities in prison are still common. The results of this reaserch indicate that the problematic fulfillment of that right was found in the form of various obstacles faced by persons with disabilities in all correctional business processes. Both the constraints of physical facilities and infrastructure, regulatory constraints, and human resource constraints. This situation is also exacerbated by the reality of overcapacity experienced by all correctional institutions in Indonesia. This research is a form of nondoctrinal research, where the data used are primary data by looking at the reality of fulfilling the rights of persons with disabilities in prison and interviewing several related parties